Goal : to double the rate of Hispanics earning a bachelor's degree - Vernez, Georges; Mizell, Lee.; RAND Education (Institute); Program for Research on Immigration Policy (U.S.); Rand Corporation; Hispanic Scholarship Fund.; Lilly Endowment (Santa Monica, CA : RAND, 2001)
The level of education Hispanics achieve will largely determine whether their role is commensurate with their demographic importance and whether they partake in the full benefits of living in the United States. Doubling the rate of Hispanics earning a bachelor's degree will have both public benefits--revenues saved in public welfare, health, and law enforcement program and revenues earned from increased taxes and contribution to Medicare and Social Security--and private benefits in terms of more disposable income. Within 13 to 15 years, the public can recoup its investment in higher education for Hispanics at a benefit-to-cost ratio of 2 to 1, and 4 to 1 if private benefits are included. Among this book's recommendations: Raise public awareness of the need for greater investments in postsecondary education; pay as much attention to keeping students in college as is currently given to preventing high school dropouts; increase the capacity of the nation's postsecondary institutions, especially in those states with high concentrations of Hispanics; coordinate interventions across all levels; and support expansion of high school-, community-, and college-based programs for at-risk students.
"RAND Education -- Center for Research on Immigration Policy."
Includes bibliographical references (p. 47-48).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Academic achievement -- United States; Hispanic American college students -- United States; Hispanic Americans -- Education (Higher) -- United States; Hispanic Americans -- Education -- United States